2005
DOI: 10.1063/1.1928367
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of a Xe cluster plasma produced by an intense ultrashort pulse KrF laser

Abstract: The dynamics of Xe clusters with initial radius between 10 and 100 Å irradiated by an IR subpicosecond laser pulse is investigated. The evolution of the cluster is modeled with a relativistic time-dependent three-dimensional particle simulation model. The focus of this investigation is to understand the energy absorption of clusters and how the absorbed energy is distributed among the various degrees of freedom. The consequence of the initial cluster radius on the absorbed energy, average charge per atom, mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
54
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(58 citation statements)
references
References 20 publications
4
54
0
Order By: Relevance
“…Theoretical studies have proven useful and capable of elucidating many aspects of the laser-cluster interaction. A wide variety of models, spatially averaged, 4 one-dimensional fluid models, 5,6 particle-in-cell codes, [7][8][9][10][11][12][13][14][15][16][17][18] and Monte Carlo simulations 19 have been developed and applied to a variety of cluster attributes. Particle simulation models, especially three-dimensional ͑3D͒, turned out to be particularly insightful.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical studies have proven useful and capable of elucidating many aspects of the laser-cluster interaction. A wide variety of models, spatially averaged, 4 one-dimensional fluid models, 5,6 particle-in-cell codes, [7][8][9][10][11][12][13][14][15][16][17][18] and Monte Carlo simulations 19 have been developed and applied to a variety of cluster attributes. Particle simulation models, especially three-dimensional ͑3D͒, turned out to be particularly insightful.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up article, we explored the effect of initial cluster radius upon the absorbed energy, average charge per atom, mean electron and ion energies, ionization, removal of electrons from the cluster, and cluster expansion. 18 This study is relevant since cluster size varies; i.e., there is certain cluster size distribution. It was found that clusters have different properties than do individual atoms: the absorbed energy per cluster scales as N 5/3 , and the mean electron and ion energy scale as N 1/3 and N 2/3 , respectively ͑N is the number of atoms per cluster͒.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction of short laser pulses with Ar and Kr clusters was modeled using a 3D relativistic molecular dynamics (MD) code [27,28]. The model accounts for plasma formation within the cluster, coupling of laser energy to the plasma and plasma evolution.…”
Section: Theoretical Modeling Of Interaction Of Short Laser Pulses Wimentioning
confidence: 99%
“…A 3D relativistic Molecular Dynamics (MD) code [16,17] was used for modeling the interaction of fs laser pulses with Xe clusters. The plasma formation within the cluster, coupling of laser energy to the plasma, and plasma evolution are all intricate parts of the model.…”
Section: Theoretical Modeling Of Interaction Of Sub-ps Laser Pulsmentioning
confidence: 99%